ANALISIS TINGKAT KESIAPAN PENGGUNA E-LEARNING UNIVERSITAS KUNINGAN DENGAN MENGGUNAKAN MODEL TECHONOLOGY READINESS INDEX (TRI) - Fahmi Yusuf; Tri Septiar Syamfithriani; Nita Mirantika (NUANSA INFORMATIKA, 2020)
Readiness in adopting new technology, especially in Online Learning in a certain University, is determined by user’s readiness i.e. the User in Online Learning.  In Kuningan University, we have concern in e-class: Online learning System, which is categorized as a new technology. The research is to analyze the user’s readiness and to measure the success of the e learning applied in our University. The method that we use in this research to measure user’s readiness level is the Technology Readiness Index (TRI). TRI is an index to measure the User’s readiness in using new technology to achieve the daily learning. The measurement is done by using four variables ; optimism, innovativeness, discomfort and insecurity. We use SPSS 21 application to analyze our data. The Research data is collected by giving Questioners to 371 respondents in Kuningan University (UNIKU). After we had calculated the data, we got the result that the TRI total value was 2.81 (categorized as Low Technology Readiness Index) and the user group was categorized as Skeptics Group (the optimism, innovativeness, discomfort and insecurity were low. These made the students of Kuningan University had uncertain feeling towards the e-class.Key words: Technology readiness index, e-learning, LMS